The Effect of Kinesiotaping on Ankle Functional Performance in Male Adolescent Futsal Athletes with Previous Ankle Sprain - Dominggus Ruku Yudit Pramono; Yustina Kristiangsih; Yunita Wiguna (Universitas Negeri Surabaya, 2026)
Background: Ankle sprain is one of the most common injuries among futsal athletes, particularly in adolescent players who frequently perform rapid and explosive changes of direction during play. This injury can reduce ankle joint stability and negatively affect athletes’ functional performance. One intervention commonly used in sports physiotherapy to improve joint stability and function is kinesiotaping. This study aimed to determine the effect of kinesiotaping on the improvement of ankle functional performance in male adolescent futsal athletes with a history of ankle sprain. Methods: This study employed a pre-experimental design with a pre-test and post-test approach. The sample consisted of 25 adolescent futsal athletes, selected using a total sampling technique. Ankle functional performance was measured before and after the application of kinesiotaping using an ankle functional performance measurement instrument. Data were analyzed using a paired sample t-test after conducting a normality test. Results: The results showed an increase in the mean ankle functional performance after the application of kinesiotaping. The mean pre-test score was 93.16 ± 7.84 cm, which increased to 105.48 ± 8.62 cm in the post-test, with an average improvement of 12.32 cm. Statistical analysis showed a p-value of 0.000 (p < 0.05), indicating a significant effect of kinesiotaping on the improvement of ankle functional performance. Conclusions: The application of kinesiotaping has been shown to have a significant effect in improving ankle functional performance in adolescent futsal athletes with a history of ankle sprain. This intervention can be used as a supportive method in injury prevention programs and performance enhancement for futsal athletes.